The Myth That Made Us: How False Beliefs about Racism and Meritocracy Broke Our Economy (and How to Fix It) - Vosters, Kelly (Journal of Economic Literature, 2023)
Kelly Vosters of University of North Carolina at Charlotte reviews “The Myth That Made Us: How False Beliefs about Racism and Meritocracy Broke Our Economy (and How to Fix It)” by Jeff Fuhrer. The Econlit abstract of this book begins: “Examines the ways that false narratives concerning race, poverty, and the sources of success in the United States negatively affect the economy, detailing how those with wealth and power have used such narratives to maintain the status quo in a system that slants outcomes toward the already successful.”